Motivación laboral y la función pública en la Dirección Regional de la Producción de Loreto 2023 - Chávez Acosta, Gustavo (2023)
An investigation was carried out with the objective of determining the relationship between work motivation and public function in the Regional Directorate of Production of Loreto, 2023. The study was descriptive and correlational with a non-experimental design. The study population consisted of 50 workers to whom a survey was applied accompanied by a questionnaire to collect the data. Therefore, the following results have been obtained where the labor motivation of the workers is average (28%). Regarding the public function, it is qualified as regular (28%). Finally, it has been possible to determine that there is a significant relationship between work motivation and public function, which has been corroborated by a coefficient of (0.867), being considerable positive and a sig (0.000). Likewise, a considerable positive relationship is established between the intrinsic motivation dimension (r= 0.736; p= 0.000), the extrinsic motivation dimension (r= 0.731; p= 0.000), and the transcendental motivation dimension (r= 0.791; p= 0.000). all these dimensions are significantly related to public service.